Analisis Swot Untuk Menentukan Strategi Pengembangan Industri Mebel - Sasongko, Lukman; , Indah Pratiwi, S.T., M.T; , Muchlison Anis S.T.,M.T (2015)
The furniture industry is an industry where its resources come from nature itself, namely wood and rattan combined with elements of the original culture of Indonesia. Kelurahan mill has a central market area around the largest furniture Surakarta then had a great chance to develop. The aim of this study was to determine the appropriate strategy for developing the furniture industry. This study uses the SWOT method is a corporate strategy to business strategy planning in the short term and long term. IFAS (Internal Strategic Factor Analysis Summary) which is a factor of a company's internal strategy that contains the strengths and weaknesses of the company. EFAS (External Strategic Factor Analysis Summary) are factors external strategy company that provides opportunities and threats. In the proposed strategies are four proposed strategies are SO strategy is to use force to take advantage of opportunities to use if the company is in cell 1, WO strategy is to minimize the weaknesses to take advantage of opportunities to use if the company is in cell 3, ST strategy is to use force to overcome the threat of use if the company is in cell 2, WT strategy is to minimize weaknesses and avoid threats used if the company is in cell 4. Results of the research with the SWOT method with the value IFAS EFAS value is 2.84 and 2.88. On the SWOT diagram Cartesian line position is in cell 2 is to support the diversification strategy used is the strategy ST. Keywords: Furniture Industry, SWOT, EFAS, IFAS